Clinical profile and lifestyle factors in women with different severities of hirsutism - Betkerur, Sagarika; Nandan, Neetha; Rajesh, Aparna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hirsutism is excessive hair growth in androgen dependent areas in women. It is noted in 10% women in the reproductive age group. Aim of the study was to identify the clinical profile and cause for hirsutism and to assess the role of diet and lifestyle factors in hirsute women. Methods: It is a hospital based observational study. A total of 300 women in reproductive age group were given a self-administered pictorial representation for scoring according to modified Ferriman-Gallway score. Results: 95 participants gave a positive response of score more than 8. Examination confirmed 85 participants had hirsutism, out of which 63 had mild hirsutism, 22 had moderate hirsutism and none had severe hirsutism. Polycystic ovarian syndrome (54.5%) was the major cause in moderate hirsutism. Features of hyperandrogenism (53%) were more prevalent in moderate hirsutism. Most of participants (31.6%) with moderate hirsutism used multiple methods for removal of hair like waxing, shaving and threading. Women with moderate hirsutism had outside food more frequently and had more of meat, fried items, alcohol. Social impact was significantly more in women with moderate hirsutism. Conclusions: Polycystic ovarian syndrome is a major cause for moderate hirsutism and they had more features of hyperandrogenism. The preferred method of hair removal is waxing and multiple methods were often used by those having moderate hirsutism. Consumption of more of non-vegetarian food, fired food and alcohol was significant in moderate hirsute women. The study underscores the importance of diet and lifestyle factors in women suffering with hirsutism.